BE_ZIVILSTRAF BK 2020 367 vom 2. September 2020 - BE Obergericht (2020)
Nichtanhandnahme Strafverfahren mit Sachverhalt gemäss Schreiben vom 10. August 2020, 15. August 2020 und 18. August 2020 | Einstellung/Nichtanhandnahme